The effect of auriculotherapy on mother-infant attachment: A clinical trial - Fatemeh Torkian; Mahboubeh Valiani; Zahra Sadat Allameh (Tehran University of Medical Sciences, 2023)
Background & Aim: Establishing effective communication and forming a strong attachment with a newborn baby are crucial tasks during the postpartum period. The bond between mother and baby has a profound impact on the child's well-being, as well as the mother's health. The aim of the present study was to investigate the effect of auriculotherapy on the mother-infant attachment. Methods & Materials: This randomized controlled clinical trial was conducted between March 2021 and September 2022 on a sample of 106 pregnant women who referred to the maternity ward of Shahid Sadoughi Hospital in Isfahan for normal vaginal delivery. The participants were randomly assigned to either the intervention group, which received auriculotherapy in addition to routine care, or the control group, which received only routine care. Auriculotherapy involved the stimulation of specific acupuncture points including oxytocin, uterus, Shen Men, thalamic, lung 1, and lung 2. Data collection was carried out using a checklist of demographic characteristics and the Maternal Postnatal Attachment Scale. Statistical analysis was performed using SPSS software version 26, employing independent t-test, paired t-test, exact Fisher's test, and chi-square test. A significance level of P<0.05 was considered statistically significant. Results: The results showed that there was no statistically significant differences observed in demographic variables between the intervention and control groups (P>0.05). However, the mean score of attachment after delivery in the auriculotherapy group was significantly higher compared to the control group (P=0.004). Conclusion: Based on the findings of this study, it has been determined that auriculotherapy exhibits the potential to enhance maternal attachment to the baby. Given its ease of use and non-invasive nature, it is strongly recommended to consider incorporating auriculotherapy as an intervention to improve mother-baby attachment during the postpartum period. Clinical trial registry: IRCT20091219002889N12